Extrafollicular Adenomatoid Odontogenic Tumor: A Case Report - Nilofar S Zaidi; Lata M Kale; Sneha H Choudhary; Vishwas Kadam (Wolters Kluwer Medknow Publications, 2017)
Odontogenic tumors are a group of heterogeneous lesions. Adenomatoid odontogenic tumor (AOT) is a benign, hamartomatous, slow-growing lesion, which is usually located in the anterior maxilla and is more prevalent in females. Although the follicular type is more frequently described in literature, here we report a case of extrafollicular type of AOT in the maxillary anterior region in a 16-year-old female.